2001
DOI: 10.1080/13576500042000197
|View full text |Cite
|
Sign up to set email alerts
|

Hand preferences in sign-learning students with autistic disorder

Abstract: The purpose of the study was fourfold: (a) to document the hand preferences of nonspeaking individuals with autism as they produced signs and nonsign actions; (b) to find out if sign-language proficiency in such individuals is associated with directionality or consistency of signing hand preference; (c) to explore the link between hand preference for signing and standardised measures of cognitive and motor development; (d) to compare the hand preferences (sign and nonsign actions) of such individuals to sign-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…(1986) showed that infants and toddlers perform symbolic activities (games like pretending to pick up the telephone) and pointing more frequently with their right hand than they do manipulative actions. Moreover, autistic children (who have difficulty communicating) do not seem to display this more pronounced right‐handed preference, and it could be because their communicative gestures are less lateralized than those reported in the general population (Bonvillian, Gershoff, Seal & Richards, 2001).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…(1986) showed that infants and toddlers perform symbolic activities (games like pretending to pick up the telephone) and pointing more frequently with their right hand than they do manipulative actions. Moreover, autistic children (who have difficulty communicating) do not seem to display this more pronounced right‐handed preference, and it could be because their communicative gestures are less lateralized than those reported in the general population (Bonvillian, Gershoff, Seal & Richards, 2001).…”
Section: Introductionmentioning
confidence: 84%
“…The experimenter sat in front of the participant for the handedness tests, and to avoid a laterality bias, stood behind him/her for the pointing tasks (e.g. Bonvillian et al ., 2001). The experimenter alternated between the use of the right and left hands when she held the book from behind the participant.…”
Section: Apparatusmentioning
confidence: 99%